The Effect Of Special Exercises Using A Creative Apparatus On Some Kinematical Variables In Performing And Achieving 110m Running the Hurdles For 14 – 17 Years Old Hurdlers - Subhi, Deyaa (Journal of Physical Education, 2018)
The research aimed at designing special exercises using creative apparatus for identifying the effect of these exercises on some kinematical variables of before hurdle phase and achievement. The researcher hypothesized significant statistical differences in kinematical variables during this phase before and after using these special exercises. The researchers used the experimental method and the subjects were the national center for gifted in Athletics aged 14 – 17 years old. The exercises were applied for 5 weeks with four training units per week for 40 – 45 minutes. The data was collected and treated using proper statistical operation to conclude that the special exercises using the creative apparatus was very effective on developing performance. Finally the researchers recommended diagnosing weaknesses and errors for each runner to find solutions for them.